Selected Abstracts of the 8th International Congress of UENPS; Bucharest (Romania); October 3rd-5th 2018; Session "Follow-up programs for high risk neonates" - - (Hygeia Press di Corridori Marinella, 2018)
Selected Abstracts of the 8th International Congress of UENPS; Bucharest (Romania); October 3rd-5th 2018; Session "Follow-up programs for high risk neonates" ABS 1. ENDOTHELIAL MICROPARTICLES AND ENDOTHELIAL PROGENITOR CELLS IN PREPUBERTAL CHILDREN BORN PREMATURELY. ASSOCIATIONS WITH CARDIOVASCULAR RISK FACTORS • P. Markopoulou, E. Papanikolaou, P. Galina, S. Loukopoulou, T. Siahanidou ABS 2. MATERNAL PERSPECTIVES ON QUALITY OF LIFE IN A GROUP OF HIGH-RISK PREMATURE INFANTS • A.R. Bivoleanu, A.L. Avasiloaiei, M. Stamatin ABS 3. ARE THERE DIFFERENCES IN THYROID FUNCTION BETWEEN INFANTS CONCEIVED BY IN VITRO FERTILIZATION AND NATURALLY CONCEIVED INFANTS? • P. Georgiadou, S. Karagianni, K. Karachristou, P. Girginoudis, A. Voutetakis, D. Platis, A. Skiathitou, C. Kanaka-Gantenbein, T. Siahanidou ABS 4. NORMAL EXAMINATION FINDINGS AT 2 YEARS CORRECTED AGE DOES NOT PREDICT NORMAL DEVELOPMENT AT 5 YEARS IN THE CASE OF EXTREMELY PREMATURE INFANTS • A.I. Toma ABS 5. SURVIVAL RATES AND NEURODEVELOPMENTAL OUTCOME AMONG EXTREMELY PRETERM INFANTS (≤ 28 WEEKS) IN NORTHWEST (NW) GREECE: A 16-YEAR REVIEW • A. Drougia, M. Baltogianni, N. Krallis, T. Gouvias, I. Nakou, N. Bega, M. Tzoufi, V. Giapros ABS 6. BRAIN ULTRASOUND AND MRI FINDINGS IN NEONATES WITH A HISTORY OF CHORIOAMNIONITIS • K. Karachristou, V. Dermetzoglou, A. Vontzalidis, E. Yatrakou, K. Katexi, A. Moutafi, V. Grigoraki, V. Galiaki ABS 7. DISORDERS OF COAGULATION IN PRETERM AND TERM NEONATES WITH CONGENITAL HEART DISEASE: PRESENTATION OF PRELIMINARY RESULTS • P. Papadogeorgou, S. Valsami, N. Iacovidou, M. Boutsikou, Th. Boutsikou, M. Politou, H. Platokouki, E. Bouza ABS 8. EVALUATION OF MODERATE AND SEVERE PHYSICAL FUNCTIONING LIMITATIONS AMONG EXTREMELY LOW BIRTH WEIGHT INFANTS (BORN BEFORE 28 WEEKS OF GESTATION) 2015-2016 IN LATVIA • A. Smildzere, G. Dzene ABS 9. EVALUATION OF PLATELET FUNCTION WITH PFA-100 IN NEONATES OF PREGNANCIES COMPLICATED WITH GESTATIONAL DIABETES • V. Mougiou, M. Politou, M. Kollia, E. Isaakidou, M. Boutsikou, Z. Iliodromiti, R. Sokou, N. Iacovidou, S. Valsami, T. Boutsikou ABS 10. IS AUTISTIC SPECTRUM DISORDER IN PRETERM CHILDREN THE SAME ENTITY AS IN TERM CHILDREN? • E. Tsekoura, X. Loseva ABS 11. LATE PRETERM NEONATES. A SPECIAL POPULATION WITH INCREASED MORBIDITY • A. Konstantinidi, R. Sokou, G. Katsaras, E. Tavoulari, S. Parastatidou, M. Kollia, E. Isaakidou ABS 12. PERINATAL PATHOLOGY ASSOCIATED WITH LONG-TERM RISK FOR FUNCTIONAL BOWEL DISORDERS IN FIRST YEAR OF LIFE • A. Babintseva, O. Godovanets ABS 13. THE ANALYSIS OF MEDICAL SERVICES, STAFF AND EQUIPMENT IN NEWBORN WARDS AND OBSTETRICS UNITS IN ROMANIA • G. Alexandrescu, A. Stănescu, I. Gussi, A. Clapa, C. Grădinaru, A. Stoian, M. Dănescu ABS 14. THE EFFECT OF MATERNAL PRE-ECLAMPSIA ON NEONATAL OUTCOME • M. Matyas, M. Hasmasanu, D. Rusu, O. Kovacs, G. Zaharie ABS 15. MORBIDITY IN EARLY TERM AND FULL-TERM NEONATES IN A NICU • R. Sokou, A. Konstantinidi, G. Katsaras, E. Tavoulari, K. Mitropoulos, V. Mougiou ABS 16. NEURODEVELOPMENTAL ASSESSMENT OF NEWBORNS WITH SEVERE HYPERBILIRUBINEMIA • E. Benderlioglu, B. Atasay, E. Ozalp, E. Okulu, G. Tunc, E. Kose, B. Bingoler, O. Erdeve, I. Ertem, S. Arsan ABS 17. PLATELET FUNCTION ASSESSMENT VIA PFA-100 IN NEONATES WITH PERINATAL HYPOXIA/ASPHYXIA • E. Isaakidou, M. Politou, N. Iacovidou, M. Kollia, V. Mougiou, R. Sokou, M. Boutsikou, Z. Iliodromiti, T. Boutsikou, S. Valsami ABS 18. AETIOLOGY AND OUTCOMES OF BABIES BORN WITH HYDROPS FETALIS IN A TERTIARY NEONATAL UNIT • R. Prasad, L. Malpas, M. Borooah ABS 19. NEONATAL JAUNDICE DUE TO HEREDITARY SPHEROCYTOSIS: A CASE REPORT • V. Mougiou, T. Boutsikou, R. Sokou, Z. Iliodromiti, M. Kollia, G. Kafalidis, N. Iacovidou ABS 20. NEONATAL TACHYARRHYTHMIAS IN A NEONATAL INTENSIVE CARE UNIT OF A TERTIARY HOSPITAL • A. Giannakopoulou, F. Anatolitou, N. Eleftherakis, C. Petropoulou, N. Lipsou, C. Chatzikonstantinou, A. Koutroumpa, E. Karanasios, H. Bouza ABS 21. PLATELET FUNCTION ASSESSMENT VIA PFA-100 IN NEONATES WITH INTRAUTERINE GROWTH RESTRICTION (IUGR) • M. Kollia, M. Politou, M. Boutsikou, E. Isaakidou, V. Mougiou, T. Boutsikou, R. Sokou, N. Iacovidou, S. Valsami ABS 22. DURAL SINUS MALFORMATION IN A NEONATE-LONG TERM FOLLOW UP • C. Petropoulou, V. Dermentzoglou, H. Bouza ABS 23. INCIDENCE OF URINARY INFECTIONS IN NEWBORNS WITH CONGENITAL HYDRONEPHROSIS • N. Lungu, A. Manea, D. Cioboata, O. Costescu, F. Doandes, M. Boia ABS 24. MOTOR DEVELOPMENT OF EARLY TERM INFANTS ASSESSED BY THE ALBERTA INFANT MOTOR SCALE • D. Syrengelas, I. Nikaina, P. Kleisiouni, T. Siahanidou ABS 25. NEURODEVELOPMENT EVALUATION AT FIRST YEAR OF LIFE OF PRETERM NEONATES WITH CONGENITAL HEART DISEASE - PRELIMINARY STUDY • F. Anatolitou, A. Giannakopoulou, N. Lipsou, S. Bouda, C. Petropoulou, A. Koutroumpa, E. Karanasios, H. Bouza ABS 26. NON-COMPACTION CARDIOMYOPATHY IN A NEONATE • A.E. Giannakopoulou, A. Komnou, E.S. Karanasios ABS 27. PRETERM INFANT FROM COMPLICATED MONOCHORIONIC TWIN PREGNANCY WITH ACUTE KIDNEY INJURY DUE TO ANTENATAL AND POSTNATAL FACTORS • R. Zarina, A. Smildzere ABS 28. UMBILICAL CORD-DERIVED STEM CELLS FOR THE PREVENTION AND TREATMENT OF BRAIN INJURY AS A CONSEQUENCE OF PRETERM BIRTH: SYSTEMATIC LITERATURE REVIEW • V.M. Samedi, L. Allahverdiyeva, K. Mohammad, H. Amin ABS 29. CONGENITAL HYPOPITUITARISM MANIFESTED AS REFRACTORY HYPOGLYCAEMIA IN A NEONATE BORN SGA • I. Vasilakis, T. Siahanidou, T. Boutsikou, A. Skiathitou, A. Sertedaki, K. Panoulis, N. Iacovidou, C. Kanaka-Gantenbein ABS 30. PREVALENCE OF ATRIAL FLUTTER IN A NEONATAL INTENSIVE CARE UNIT OF A TERTIARY HOSPITAL • A. Giannakopoulou, N. Eleftherakis, F. Anatolitou, N. Lipsou, C. Petropoulou, A. Koutroumpa, E. Karanasios, H. Bouza ABS 31. TWO PHENOTYPES... THE SAME DISEASE • T. Pereira, D. Pinto, N.O. Teles, A.M. Fortuna, M. Azevedo ABS 32. STURGE-WEBER-KRABBE SYNDROME - THE IMPORTANCE OF AN EARLY DIAGNOSTIC AND FOLLOW-UP PROTOCOL - A SERIES OF CASE REPORTS • I. Streata, A. Burlacu, M. Lupu, S. Nita, M. Sandu, R. Teleanu ABS 33. CONSIDERATIONS REGARDING THE NEONATAL EVOLUTION OF THE PREMATURE INFANT WITH INTRAUTERINE GROWTH RESTRICTION WITH GESTATIONAL AGE BELOW 32 WEEKS • M. Tunescu, G. Olariu ABS 34. DOUBLE SURGICAL PATHOLOGY IN A PRETERM INFANT • I. Rosca, R. Tocariu, M. Şerban, O. Şaulea, C.C. Babei ABS 35. CAUSES OF INFANT MORTALITY IN CROATIA AND THE EUROPEAN UNION IN THE PERIOD 2011-2015 • Ž. Draušnik, I. Cerovečki, U. Rodin